Anthropogenic Disturbance Impacts Mycorrhizal Communities and Abiotic Soil Properties: Implications for an Endemic Forest Disease - Sapsford, Sarah J.; Paap, Trudy; Hardy, Giles E. St. J.; Burgess, Treena I. (Frontiers in Forests and Global Change, 2021)
In forest ecosystems, habitat fragmentation negatively impacts stand structure and biodiversity; the resulting fragmented patches of forest have distinct, disturbed edge habitats that experience different environmental conditions than the interiors of the fragments. In southwest Western Australia, there is a large-scale decline of the keystone tree species Corymbia calophylla following fragmentation and land use change. These changes have altered stand structure and increased their susceptibility to an endemic fungal pathogen, Quambalaria coyrecup, which causes chronic canker disease especially along disturbed forest habitats. However, the impacts of fragmentation on belowground processes in this system are not well understood. We examined the eaffects of fragmentation on abiotic soil characteristics properties and ectomycorrhizal (ECM) and arbuscular mycorrhizal fungal (AMF) communities, and whether these belowground changes were drivers of disease incidence. We collected soil from 17 sites across the distribution range of C. calophylla. Soils were collected across a gradient from disturbed, diseased areas to undisturbed, disease-free areas. We analysed soil nutrients and grew C. calophylla plants as a bioassay host. Seedlings were harvested and roots collected after six months of growth. DNA was extracted from the roots, amplified using fungal specific primers and sequenced using Illumina MiSeq. Concentrations of key soil nutrients such as nitrogen, phosphorus and potassium were much higher along the disturbed, diseased edges in comparison to undisturbed areas. Disturbance altered the community composition of ECMmycorrhizal and AMFfungi:; however, only ECM communities had lower rarefied richness and diversity along the disturbed, diseased areas compared to undisturbed areas. Accounting for effects of disturbance, ECM diversitypotassium and leaf litter depth were highly correlated with increased disease incidence in C. calophylla. In the face of global change, increased virulence of an endemic pathogen has emerged in this Mediterranean-type forest.